2021
DOI: 10.14256/jce.2738.2019
|View full text |Cite
|
Sign up to set email alerts
|

Construction cost estimation of reinforced and prestressed concrete bridges using machine learning

Abstract: Seven state-of-the-art machine learning techniques for estimation of construction costs of reinforced-concrete and prestressed concrete bridges are investigated in this paper, including artificial neural networks (ANN) and ensembles of ANNs, regression tree ensembles (random forests, boosted and bagged regression trees), support vector regression (SVR) method, and Gaussian process regression (GPR). A database of construction costs and design characteristics for 181 reinforced-concrete and prestressed-concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In the implementation of RF, it is recommended that the number of randomly selected variables be approximately equal to one-third of the total number of variables, which in most problems should lead to a satisfactory model. Such assumptions have been adopted in the program implementation in the MATLAB 2020a program (default settings) [21,25]. In this case, it would mean the adoption of models which generate regression trees using two or three variables out of the seven variables, which is not fully accepted in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the implementation of RF, it is recommended that the number of randomly selected variables be approximately equal to one-third of the total number of variables, which in most problems should lead to a satisfactory model. Such assumptions have been adopted in the program implementation in the MATLAB 2020a program (default settings) [21,25]. In this case, it would mean the adoption of models which generate regression trees using two or three variables out of the seven variables, which is not fully accepted in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Splits in the model are only performed on these variables. If p is the total number of input variables or predictors in the training data, the algorithm will narrow the selection to m = p / 3 variables when selecting a new branching variable [21,25]. For each branching, a new random sample of variables is taken into consideration.…”
Section: Regression Tree Ensemblesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, both nationally and internationally, the construction of bridges has steadily increased. On the eastern and southern branches of highway Corridor X in Serbia, contracts for the construction of about 200 reinforced concrete bridges totaling more than 100 million euros were signed from 2009 to 2015 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…To offer guidance on establishing the upper limit for neurons in the hidden layer, the research provides recommended expressions ( 16) and ( 17), with a preference indicated for smaller values. These recommendations (24), (25) serve as valuable insights for the meticulous optimization of the neural network architecture, ensuring its efficacy in predicting compressive strength [37,42]. The value of the parameter λ k (Mu) 0.005 1.00 × 10 10…”
mentioning
confidence: 99%